Dynamics of Debt and Asset Management in the Construction of Traditional Houses of the Bineke Tribe, Malaka Regency - Mau, Ignatia Thomasita Bau; Wutun, Maria B. Mawarni G.; Hendrikus , Hedwigh (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2025)
This study uses a qualitative method with a phenomenological approach to analyze debt and asset management in the Bineke tribe community related to the construction of traditional houses. Data were collected through semi-structured interviews with key informants, such as traditional leaders and financial managers, as well as supporting informants for data validation. Informant identities were coded to maintain confidentiality. The results of the study indicate that the simultaneous construction of traditional houses creates great financial pressure, pushing tribe members into debt without a clear repayment strategy. Meanwhile, assets such as land, rice fields, gardens, and livestock have not been optimally utilized as sources of income. Lack of understanding of financial management causes the debt cycle to repeat itself. Therefore, education and reform are needed in the traditional financing system so that a balance between cultural preservation and economic welfare can be achieved.